Technology and Innovation Transformation Toward Food Security Resilience: A Systematic Literature Review of Global Agricultural Strategies in the Digital Era - Usmiati; Said, Laila Refiana; Rifani, Ahmad; Huda, Nuril; Fitriansyah, Ricky (Journal of Scientific Insights, 2025)
Technological transformation and innovation are strategically important in increasing food security, particularly through integrating digital marketing approaches in the global agribusiness system. As the digital era develops, agricultural marketing strategies focus on product distribution and include value creation, information technology adaptation, and digital consumer engagement. This study aims to systematically review the global literature on technology-based agricultural strategies that support food security. This article uses the Systematic Literature Review (SLR) approach to identify key trends, dominant theories, and research gaps in integrating marketing strategies and technological innovation in digital agriculture. The study results show that the relationship between technological transformation, marketing innovation, and food security is still not widely discussed in a single conceptual framework. Therefore, this study offers a theoretical contribution in the form of strengthening the perspective of digital agromarketing that supports the food system's resilience through technology optimization. The practical implications are directing stakeholders in the public and private sectors to formulate data-driven and collaborative marketing strategies to address food security challenges sustainably in the digital age.